Rubber boots methods for the anthropocene : doing fieldwork in multispecies worlds - Bubandt, Nils; Andersen, Astrid Oberborbeck; Cypher, Rachel Antoinette, 1985- (University of Minnesota Press, 2022)
"Answering methodological challenges posed by the Anthropocene, this collection retools the empirical study of the socioecological chaos of the contemporary moment across the arts, human science, and natural science. The methodological companion to Arts of Living on a Damaged Planet, it provides empirical studies of the multispecies messiness of contemporary life that investigate some of the critical questions of our time"--